2020
DOI: 10.1128/mcb.00492-19
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between HuR and circPABPN1 Modulates Autophagy in the Intestinal Epithelium by Altering ATG16L1 Translation

Abstract: Intestinal epithelial autophagy is crucial for host defense against invasive pathogens, and defects in this process occur frequently in patients with inflammatory bowel disease (IBD) and other mucosal disorders, but the exact mechanism that activates autophagy is poorly defined. Here, we investigated the role of RNA-binding protein HuR (human antigen R) in the posttranscriptional control of autophagy-related genes (ATGs) in the intestinal epithelium. We found that targeted deletion of HuR in intestinal epithel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
71
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(74 citation statements)
references
References 60 publications
2
71
0
1
Order By: Relevance
“…By ribonucleotide immunoprecipitation it was demonstrated the interaction of HuR with ATG5, ATG12, and ATG16 mRNAs; HuR binds to AU-rich elements (AREs) located at the 3'UTR of these mRNAs (50). That HuR enhances ATG16 mRNA translation was also demonstrated in intestinal epithelium cells in vitro and in vivo in a mice line with intestinal epithelium-specific ablation of HuR (IE-HuR −/− ); human intestinal mucosa from patients with Inflammatory Bowel Disease exhibit decreased levels of both HuR and ATG16L1, this is an interesting finding since autophagy is frequently defective in those patients (53). HuR induction of ATG7 and ATG16 mRNA translation was demonstrated in renal proximal tubular cells during hypoxiainduced autophagy; HuR binds to motifs located within ATG7 mRNA coding region (51).…”
Section: Rna Binding Proteins Control Autophagymentioning
confidence: 89%
See 1 more Smart Citation
“…By ribonucleotide immunoprecipitation it was demonstrated the interaction of HuR with ATG5, ATG12, and ATG16 mRNAs; HuR binds to AU-rich elements (AREs) located at the 3'UTR of these mRNAs (50). That HuR enhances ATG16 mRNA translation was also demonstrated in intestinal epithelium cells in vitro and in vivo in a mice line with intestinal epithelium-specific ablation of HuR (IE-HuR −/− ); human intestinal mucosa from patients with Inflammatory Bowel Disease exhibit decreased levels of both HuR and ATG16L1, this is an interesting finding since autophagy is frequently defective in those patients (53). HuR induction of ATG7 and ATG16 mRNA translation was demonstrated in renal proximal tubular cells during hypoxiainduced autophagy; HuR binds to motifs located within ATG7 mRNA coding region (51).…”
Section: Rna Binding Proteins Control Autophagymentioning
confidence: 89%
“…It is currently unknown what regulates the binding of Hu proteins to target mRNAs. Recently, it was reported that the circular RNA circPABPN1 blocks the interaction between HuR and Atg16 mRNA (53). Whether other Hu/mRNA interactions are also regulated by circRNAs or other mechanisms, such as post-translational modifications (69), or whether it is constitutive under certain circumstances, need to be further studied.…”
Section: Rna Binding Proteins Control Autophagymentioning
confidence: 99%
“…RNA-binding protein human antigen R (HuR) can increase autophagy in intestinal epithelium by upregulating ATG16L1 expression via binding with ATG16L1 mRNA. circPABPN1 can downregulate ATG16L1 to inhibit autophagy by ejecting HuR [ 48 ]…”
Section: Cernas-regulated Autophagy In Cancermentioning
confidence: 99%
“…RNA pull-down and RIP assays identified the interaction between HULC and FoxM1. Silencing of HULC inhibited autophagy and reduced cisplatin resistance through regulating FoxM1 [ 48 ]. Intriguingly, HULC indirectly increased USP22 expression via epigenetic or transcriptional modulation of miR-6825-5p, miR-6845-5p, and miR-6886-3p rather than sponging these molecules in HCC cells [ 131 ].…”
Section: Cerna-mediated Autophagy and Chemoresistancementioning
confidence: 99%
“…CircRNAs can also act as miRNA 'sponge', a feature that is to date limited to about ten circRNAs genome-wide in humans (Guo et al, 2014;Piwecka et al, 2017;Stagsted et al, 2019). In addition, circRNA-mediated regulation of mRNA translation has been proposed in cell lines (Li et al, 2020;Sun et al, 2019;Wu et al, 2019). Lastly, it was shown with overexpression constructs in cell lines (Legnini et al, 2017;Yang et al, 2017), and from exemplary circRNAs in drosophila and human cell lines that circRNA can be translated into protein (Liang et al, 2019;Pamudurti et al, 2017).…”
Section: Introductionmentioning
confidence: 99%